Aqueous slurry polyanion sodium ion soft pack battery and preparation method thereof

By using Na3V2-x-ySbxTiyO(PO4)2F2 polyanionic positive electrode material and pre-sodium treatment technology, the electrode sheet preparation process of sodium ion soft-pack batteries was optimized, and the technical bottleneck in the commercial application of sodium ion soft-pack batteries was solved, and the technology was achieved. High rate performance and long cycle life effect.

CN118198274BActive Publication Date: 2025-02-18NANKAI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410401660.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-02-18
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

In the prior art, the pole sheet preparation process and battery cell assembly process of sodium ion soft-pack batteries have not been fully optimized, which limits its commercial application.

Method used

The polyanionic positive electrode material with the chemical formula Na3V2-x-ySbxTiyO(PO4)2F2 was used, and the preparation process of the positive electrode sheet was optimized through pre-sodium treatment and the use of an aqueous slurry binder.

Benefits of technology

It significantly improves the rate performance and cycle life of sodium ion soft-pack batteries, achieves high energy density and stability, and is suitable for large-scale energy storage and new energy vehicles and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118198274B_ABST
    Figure CN118198274B_ABST
Patent Text Reader

Abstract

The present invention discloses a water-based slurry polyanion sodium ion soft pack battery and a preparation method thereof, and relates to the technical field of new energy materials and devices. The positive electrode sheet of the sodium ion soft pack battery of the present invention adopts a chemical formula of Na3V 2‑x‑y Sb x Ti y O(PO4)2F2 polyanion positive electrode material; wherein 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials and devices, and in particular to an aqueous slurry polyanion sodium ion soft-pack battery and a preparation method thereof. Background Art

[0002] Efficient electrochemical energy storage technologies, such as the use of lithium-ion batteries, will greatly promote the realization of the common global goal of carbon neutrality and further postpone the arrival of the foreseeable energy crisis. The demand for lithium-ion batteries continues to increase, but the raw material resources are limited, resulting in a surge in the cost of lithium-ion batteries. Sodium has similar physical and chemical properties to lithium. Sodium resources are very abundant in the earth's crust, accounting for 2.74% of the element content of the earth's crust, and are distributed all over the world without geographical restrictions. Due to these characteristics of sodium, sodium-ion batteries have become an ideal alternative to lithium-ion batteries, especially in large-scale energy storage applications.

[0003] With the continuous development of sodium-ion batteries, more and more sodium-ion full batteries have been proposed, but they are all limited to button-type full batteries in laboratory environments, and there are few studies on sodium-ion soft-pack batteries. Therefore, the development and optimization of the electrode preparation process and cell assembly process of sodium-ion soft-pack batteries are of great significance for their commercial application. Summary of the invention

[0004] The purpose of the present invention is to provide an aqueous slurry polyanion sodium ion soft pack battery and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] The present invention provides a sodium ion soft pack battery, wherein the positive electrode sheet of the sodium ion soft pack battery adopts a chemical formula of Na3V 2-x-y Sb x Ti y O(PO4)2F2 polyanion positive electrode material; wherein 0 <x≤0.2,0<y≤0.2。

[0007] Among them, the synergistic effect of co-doping Ti and Sb elements can improve the electronic conductivity and ion diffusion kinetics of the material, thereby significantly improving the rate performance and cycle life of the positive electrode material.

[0008] As a further preferred embodiment of the present invention, the positive electrode sheet adopts a chemical formula of Na3V 1.88 Sb 0.03 Ti 0.09 O(PO4)2F2 or Na3V 1.76 Sb 0.06 Ti 0.18Polyanionic positive electrode material of O(PO4)2F2.

[0009] As a further preferred embodiment of the present invention, the positive electrode plate is pre-sodium treated; the positive electrode plate uses water-based slurry as a binder.

[0010] As a further preferred embodiment of the present invention, the water-based slurry includes sodium carboxymethyl cellulose, and more preferably a combination of sodium carboxymethyl cellulose and styrene-butadiene rubber.

[0011] As a further preferred embodiment of the present invention, the negative electrode plate used in the sodium ion soft-pack battery contains a hard carbon negative electrode material.

[0012] As a further preferred embodiment of the present invention, the double-sided density of the positive electrode sheet is 25-52 mg / cm 2 The double-sided density of the negative electrode sheet is 10-20 mg / cm 2 .

[0013] The capacity of the sodium ion soft-pack battery prepared by the present invention can reach 0.4-10Ah.

[0014] As a further preferred embodiment of the present invention, the chemical formula is Na3V 2-x-y Sb x Ti y The preparation method of the polyanionic positive electrode material of O(PO4)2F2 comprises the following steps:

[0015] Vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, an antimony source and a titanium source are mixed and calcined in a protective atmosphere to obtain the chemical formula Na3V 2-x-y Sb x Ti y Polyanionic positive electrode material of O(PO4)2F2.

[0016] As a further preferred embodiment of the present invention, the calcination temperature is 500-700° C., and the calcination time is 4-10 h.

[0017] As a further preferred embodiment of the present invention, during calcination, the heating rate is controlled to be 1-5°C / min, and calcination is performed after the temperature reaches 500-700°C.

[0018] As a further preferred embodiment of the present invention, the molar ratio of the vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, antimony source and titanium source is 2-xy:2-xy:4:1:2x:2y; wherein, 0 <x≤0.2,0<y≤0.2。

[0019] Vanadyl phosphate can be prepared by the following steps: vanadium pentoxide and ammonium dihydrogen phosphate are crushed and mixed at a molar ratio of 1:2, and after being fully mixed, they are sintered in an air atmosphere at a sintering temperature of 700-800°C and a sintering time of 2-6h to obtain raw material VOPO4.

[0020] Vanadium phosphate can be prepared by the following steps: vanadium pentoxide, ammonium dihydrogen phosphate, and conductive carbon are crushed and mixed in a molar ratio of 1:2:0.2, and after being fully mixed, they are sintered in an argon atmosphere at a sintering temperature of 800-900°C and a sintering time of 2-6h to obtain raw material VPO4.

[0021] As a further preferred embodiment of the present invention, the antimony source includes one or more of antimony trioxide, antimony pentoxide or antimony acetate; and the titanium source includes titanium monoxide, titanium dioxide or titanium trioxide.

[0022] As a further preferred embodiment of the present invention, the pre-sodium treatment includes the step of soaking the positive electrode plate in a biphenyl-sodium solution or a naphthalene-sodium solution. More preferably, the concentration of the biphenyl-sodium solution or the naphthalene-sodium solution is 0.1-2 mol / L.

[0023] More specifically, the solvent of the pre-sodium solution used for the pre-sodium treatment in the present invention is an aprotic solvent, including one of ethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, and tetrahydropyran, the solute is biphenyl or naphthalene and metallic sodium, and the solution concentration is 0.1-2mol / L. The pre-sodium solution preparation method is: firstly, biphenyl or naphthalene is added to a solvent of ethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, and tetrahydropyran, and metallic sodium is added after stirring and dissolving to form a solution of biphenyl-sodium or naphthalene-sodium.

[0024] The present invention also provides a method for preparing the above-mentioned sodium ion soft-pack battery, comprising the following steps:

[0025] The positive electrode sheet and the negative electrode sheet are stacked in a Z-shaped manner, and an electrolyte is added for packaging to obtain the sodium ion soft-pack battery.

[0026] More specifically, the sodium ion soft-pack battery of the present invention includes a positive electrode sheet, a separator, a negative electrode sheet, an electrolyte, a tab, and an aluminum-plastic film package.

[0027] As a further preferred embodiment of the present invention, the preparation method of the positive electrode sheet comprises the following steps: mixing the polyanion positive electrode material, Super-P, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 91:5:2:2 and coating them on both sides of the aluminum foil, drying them under vacuum conditions at 80-120°C for 10-15h to obtain the positive electrode sheet, and rolling the positive electrode sheet to a compaction density of 2.0-2.5g / cm 3, and then die-cut to the size of (55.2mm-83mm)*(85.5mm-163mm) to obtain the positive electrode sheet.

[0028] As a further preferred embodiment of the present invention, the preparation method of the negative electrode sheet comprises the following steps: mixing the hard carbon negative electrode material, Super-P, styrene-butadiene rubber, and sodium carboxymethyl cellulose in a mass ratio of 92:3:2.5:2.5, coating the mixture on both sides of the mixture on an aluminum foil, and drying the mixture in a 60-90°C forced air drying oven for 10-15 hours to obtain a hard carbon negative electrode sheet, and rolling the negative electrode sheet to a compaction density of 1.0-1.5 g / cm 3 , and then die-cut to the size of (57.2mm-85mm)*(87.0mm-165mm) to obtain a hard carbon negative electrode sheet.

[0029] As a further preferred embodiment of the present invention, during the pre-sodium treatment, the positive electrode plate is immersed in a biphenyl-sodium solution or a naphthalene-sodium solution for 0.05-2h, then washed three times with a non-protonic solvent including one of ethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, and tetrahydropyran, and vacuum dried at 60-90°C for 8-12h to obtain a pre-sodium positive electrode plate.

[0030] As a further preferred embodiment of the present invention, during the battery preparation process, the compaction density of the positive electrode sheet is 2.0-2.5 g / cm 3 The die-cutting size is (55.2mm-83mm)*(85.5mm-163mm), and the compaction density of the negative electrode is 1.0 -1.5g / cm 3 The die-cutting size is (57.2mm-85mm)*(87.0mm-165mm). The positive and negative pole pieces with higher compaction density can realize the assembly of large-capacity soft-pack batteries.

[0031] More preferably, the sodium ion soft-pack battery of the present invention is stacked in a Z-shaped manner, by stacking 1-25 pre-sodium positive electrode sheets and 2-26 negative electrode sheets in sequence, adding electrolyte and packaging.

[0032] As a further preferred embodiment of the present invention, the electrolyte is one of 1M NaPF6〔diethanol dimethyl ether (G2) + vinylene carbonate (VC)〕〔V(G2):V(VC)=1:0.05〕and 1M NaPF6〔ethylene carbonate (EC) + dimethyl carbonate (DMC) + ethyl methyl carbonate (EMC)〕〔V(EC):V(DMC):V(EMC)=1:1:1〕.

[0033] The present invention discloses the following technical effects:

[0034] The present invention adopts a polyanion positive electrode material Na3V4 with a high operating voltage of 3.8V and good water stability. 2-x-y Sbx Ti y O(PO4)2F2, as the positive electrode material of sodium-ion soft-pack batteries, ensures the stability and energy density of the batteries.

[0035] The present invention adopts Na3V 2-x-y Sb x Ti y On the basis of O(PO4)2F2 vanadium-based polyanion positive electrode material, aqueous binders can be further used to make the electrode sheets, thereby avoiding the use of toxic and high-cost N-methylpyrrolidone solvent.

[0036] The chemical pre-sodium treatment of the positive electrode plate in the present invention can provide additional active sodium to compensate for irreversible sodium loss during the cycle of the soft-pack battery, including the capture of sodium ions by the solid electrolyte interface membrane and the negative electrode structural defects, which is beneficial to improving the cycle stability of the soft-pack battery.

[0037] The sodium ion soft-pack battery of the present invention has excellent rate performance and long cycle life, and can be widely used in the fields of large-scale energy storage and new energy vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 This is a comparison chart of the cycle performance of the sodium ion soft-pack batteries prepared in Example 1 of the present invention and Comparative Example 1;

[0040] Figure 2 The formation and first cycle charge and discharge curves of the sodium ion soft pack battery prepared in Example 1 of the present invention;

[0041] Figure 3 This is a comparison chart of the cycle performance of the sodium ion soft-pack batteries prepared in Example 1 of the present invention and Comparative Examples 3 and 4 (0.5C rate);

[0042] Figure 4 The formation and first cycle charge and discharge curves of the sodium ion soft pack battery prepared in Example 2 of the present invention;

[0043] Figure 5 The cycle performance (1C rate) of the sodium ion soft pack battery prepared in Example 2 of the present invention;

[0044] Figure 6 The formation and first cycle charge and discharge curves of the sodium ion soft pack battery prepared in Example 3 of the present invention;

[0045] Figure 7 The cycle performance (0.5C rate) of the sodium ion soft pack battery prepared in Example 3 of the present invention;

[0046] Figure 8 The formation and first cycle charge and discharge curves of the sodium ion soft pack battery prepared in Example 4 of the present invention;

[0047] Fig. 9 The cycle performance (0.1C rate) of the sodium ion soft pack battery prepared in Example 4 of the present invention;

[0048] Fig.10 This is a physical picture of the sodium ion soft pack battery prepared in Examples 1-4 of the present invention;

[0049] Fig.11 The charge and discharge curve (1C rate) of the water stability test of the positive electrode material prepared in Example 1 of the present invention;

[0050] Fig.12 This is a cycle performance diagram (1C rate) of the water stability test of the positive electrode material prepared in Example 1 of the present invention;

[0051] Fig.13 The SEM and Mapping element analysis diagrams of the positive electrode material synthesized in Experimental Example 1 of the present invention;

[0052] Fig.14 The SEM and Mapping element analysis diagrams of the positive electrode material synthesized in Experimental Example 2 of the present invention. DETAILED DESCRIPTION

[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0054] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0055] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0056] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0057] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0058] Example 1

[0059] A method for preparing a polyanion sodium ion soft pack battery, the steps are as follows:

[0060] (1) Preparation of positive electrode sheet: Active material, conductive carbon, binder 1 and binder 2 were mixed in a mass ratio of 91:5:2:2. 1.88 Sb 0.03 Ti 0.09 O(PO4)2F2 positive electrode material (active material), 25g Super-P (conductive carbon), 10g sodium carboxymethyl cellulose (binder 1) and 10g styrene-butadiene rubber (binder 2) were mixed, and the viscosity of the slurry was adjusted to 6000mPa·s by controlling the amount of deionized water added and coated on both sides of aluminum foil, and dried at 80℃ under vacuum for 12h. The mass of active material per unit area was ≈25.64mg / cm 2 Among them, Na3V 1.88 Sb 0.03 Ti 0.09 The preparation method of O(PO4)2F2 positive electrode material is as follows: vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, antimony trioxide, antimony acetate and titanium trioxide are crushed and mixed in a pulverizer at a ratio of 0.95:0.95:2:0.5:0.05:0.05 (wherein the molar ratio of antimony trioxide to antimony acetate is 1:1), and then calcined in an argon atmosphere at a sintering temperature of 600°C, a heating rate of 5°C / min, and a sintering time of 6h to obtain Na3V 1.88 Sb 0.03 Ti 0.09O(PO4)2F2 positive electrode material was characterized by ICP, which proved that the synthesized material was Sb and Ti co-doped positive electrode material.

[0061] (2) Preparation of negative electrode sheet: Weigh 460 g of hard carbon negative electrode material (active material), 15 g of Super-P (conductive carbon), 12.5 g of sodium carboxymethyl cellulose (binder 1) and 12.5 g of styrene-butadiene rubber (binder 2). Adjust the viscosity of the slurry to 5000 mPa·s by controlling the amount of deionized water added and apply it on both sides of aluminum foil. Dry it at 80 °C under vacuum for 12 h. The mass of active material per unit area is ≈12.39 mg / cm 2 .

[0062] (3) Positive and negative electrode sheet rolling: Select a 160 μm roll gap to roll the positive electrode sheet, so that the compaction density of the positive electrode sheet is 2.1 g / cm 3 ; Select a roller gap of 130 μm to roll the hard carbon negative electrode, so that the compaction density of the negative electrode sheet is 1.02 g / cm 3 After rolling, both the positive and negative electrodes show a mirror effect.

[0063] (4) Pole sheet die-cutting: The positive electrode sheet is die-cut to a positive electrode sheet with a width of 55.2 mm, a length of 85.5 mm, a tab length of 12 mm, and a width of 12 mm; the negative electrode sheet is die-cut to a negative electrode sheet with a width of 57.2 mm, a length of 87.0 mm, and a tab length of 12 mm.

[0064] (5) Pre-sodium treatment of the positive electrode: Under an inert atmosphere, 3 positive electrode sheets were immersed in a 1 mol / L biphenyl-sodium solution for 1 h, then washed 3 times with ethylene glycol dimethyl ether solution, and vacuum dried at 80 °C for 12 h to obtain pre-sodium positive electrode sheets.

[0065] (6) Preparation of sodium ion soft pack battery: stack 3 pre-sodium positive electrode plates, celgard2500 separator, and 4 negative electrode plates in a "Z-shaped" order, fix them with electrolyte-resistant tape, and weld the aluminum tabs with the tabs using an ultrasonic spot welder. After welding the tabs, place the battery cell in a semi-open aluminum plastic film for top and side sealing, and then transfer it to a vacuum oven at 80°C for drying for 6 hours; inject the electrolyte 1M NaPF6 into the battery cell after drying [ethylene carbonate (EC) + dimethyl carbonate (DMC) + ethyl methyl carbonate (EMC)] [V (EC): V (DMC): V (EMC) = 1:1:1], and obtain a polyanion sodium ion soft pack battery after packaging.

[0066] (7) Sodium ion soft-pack battery formation: The assembled soft-pack battery was placed in a 40°C vacuum oven for 12 h and then formed on a blue-power charge and discharge tester with a voltage range of 0.2-4.3 V. The formation conditions were: (1) 0.05C constant current charging to 3.8 V; (2) 0.1C constant current charging to 4.3 V; (3) 0.1C constant current discharging to 0.2 V.

[0067] Sodium ion soft pack battery test:

[0068] The formed sodium ion soft pack battery was vacuum vented and then pressurized for testing. The double-sealed battery was placed on a blue-electric charge and discharge tester for electrochemical performance testing. The cycle was carried out at a 0.5C rate, 1C = 129mA / g, and the voltage range was 1.5-4.2V.

[0069] Figure 2 The formation and 0.1C first cycle charge and discharge curves of the sodium ion soft pack battery prepared in Example 1 of the present invention. Figure 3 This is a 0.5C cycle performance diagram of the sodium ion soft-pack battery prepared in Example 1 of the present invention.

[0070] The sodium ion soft-pack battery designed in Example 1 of the present invention has a capacity of 0.5Ah, a first-cycle discharge capacity (0.1C) of 350mAh, a capacity retention rate of 94.2% after 100 cycles at 0.5C, and a mass energy density of 95.2Wh / kg.

[0071] Example 2

[0072] A method for preparing a polyanion sodium ion soft pack battery, the steps are as follows:

[0073] (1) Preparation of positive electrode sheet: Active material, conductive carbon, binder 1 and binder 2 were mixed in a mass ratio of 91:5:2:2. 1.76 Sb 0.06 Ti 0.18 O(PO4)2F2 positive electrode material (active material), 25g Super-P (conductive carbon), 10g sodium carboxymethyl cellulose (binder 1) and 10g styrene-butadiene rubber (binder 2) were mixed, and the viscosity of the slurry was adjusted to 6000mPa·s by controlling the amount of deionized water added and coated on both sides of aluminum foil. It was dried at 80℃ under vacuum for 12h, and the mass of active material per unit area was ≈48.96mg / cm 2 Among them, Na3V 1.76 Sb 0.06 Ti 0.18The preparation method of O(PO4)2F2 positive electrode material is as follows: vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, antimony trioxide, antimony acetate and titanium trioxide are crushed and mixed in a pulverizer in a ratio of 0.9:0.9:2:0.5:0.1:0.1 (wherein the molar ratio of antimony trioxide to antimony acetate is 1:1), and then calcined in an argon atmosphere at a sintering temperature of 600°C, a heating rate of 5°C / min, and a sintering time of 6h to obtain Na3V 1.76 Sb 0.06 Ti 0.18 O(PO4)2F2 positive electrode material was characterized by ICP, which proved that the synthesized material was Sb and Ti co-doped positive electrode material.

[0074] (2) Preparation of negative electrode sheet: Weigh 460 g of hard carbon negative electrode material (active material), 15 g of Super-P (conductive carbon), 12.5 g of sodium carboxymethyl cellulose (binder 1) and 12.5 g of styrene-butadiene rubber (binder 2). Adjust the viscosity of the slurry to 5000 mPa·s by controlling the amount of deionized water added and apply it on both sides of aluminum foil. Dry it at 80 °C under vacuum for 12 h. The mass of active material per unit area is ≈15.34 mg / cm 2 .

[0075] (3) Positive and negative electrode sheet rolling: Select a 160 μm roller gap to roll the positive electrode sheet, so that the compaction density of the positive electrode sheet is 2.2 g / cm 3 ; Select a roller gap of 130 μm to roll the hard carbon negative electrode, so that the compaction density of the negative electrode sheet is 1.05 g / cm 3 After rolling, both the positive and negative electrodes show a mirror effect.

[0076] (4) Pole sheet die-cutting: The positive electrode sheet is die-cut to a positive electrode sheet with a width of 55.2 mm, a length of 85.5 mm, a tab length of 12 mm, and a width of 12 mm; the negative electrode sheet is die-cut to a negative electrode sheet with a width of 57.2 mm, a length of 87.0 mm, and a tab length of 12 mm.

[0077] (5) Pre-sodium treatment of the positive electrode: Under an inert atmosphere, 4 positive electrode sheets were immersed in a 1 mol / L biphenyl-sodium solution for 1 h, then washed three times with ethylene glycol dimethyl ether solution, and vacuum dried at 80 °C for 12 h to obtain pre-sodium positive electrode sheets.

[0078] (6) Preparation of sodium ion soft pack battery: 4 pre-sodium positive electrode plates, celgard2500 separator, and 5 negative electrode plates are stacked in a "Z-shaped" order, fixed with electrolyte-resistant tape, and then welded together with the aluminum tabs and the tabs using an ultrasonic spot welder. After welding the tabs, the battery cell is placed in a semi-open aluminum plastic film for top and side sealing and then transferred to an 80°C vacuum oven for drying for 6 hours; after drying, the electrolyte is injected into the battery cell, the electrolyte concentration is 1 mol / L, the solute is sodium hexafluorophosphate, the solvent is diethylene glycol dimethyl ether (G2), the additive is vinyl carbonate (VC), V(G2):V(VC)=1:0.05, and a polyanion sodium ion soft pack battery is obtained after packaging.

[0079] (7) Sodium ion soft-pack battery formation: The assembled soft-pack battery was placed in a 40°C vacuum oven for 12 h and then formed on a blue-power charge and discharge tester with a voltage range of 0.2-4.3 V. The formation conditions were: (1) 0.05C constant current charging to 3.8 V; (2) 0.1C constant current charging to 4.3 V; (3) 0.1C constant current discharging to 0.2 V.

[0080] Sodium ion soft pack battery test:

[0081] The formed sodium ion soft pack battery was vacuum vented and then pressurized for testing. The double-sealed battery was placed on a blue-electric charge and discharge tester for electrochemical performance testing. The cycle was carried out at a 0.5C rate, 1C = 129mA / g, and the voltage range was 1.5-4.2V.

[0082] Figure 4 This is the first cycle charge and discharge curve of the sodium ion soft pack battery prepared in Example 2 of the present invention. Figure 5 The cycle performance (1C rate) of the sodium ion soft pack battery prepared in Example 2 of the present invention.

[0083] The capacity of the soft-pack battery designed in Example 2 of the present invention is 1Ah, and the capacity of the first cycle at 0.1C is 0.79Ah; after 500 cycles at a rate of 1C, the capacity retention rate is 85.7%, and the mass energy density is 114Wh / kg.

[0084] Example 3

[0085] A method for preparing a polyanion sodium ion soft pack battery, the steps are as follows:

[0086] (1) Preparation of positive electrode sheet: Active material, conductive carbon, binder 1 and binder 2 were mixed in a mass ratio of 91:5:2:2. 1.76 Sb 0.06 Ti 0.18O(PO4)2F2 positive electrode material (active material), 25g Super-P (conductive carbon), 10g sodium carboxymethyl cellulose (binder 1) and 10g styrene-butadiene rubber (binder 2) were mixed, and the viscosity of the slurry was adjusted to 6000mPa·s by controlling the amount of deionized water added and coated on both sides of aluminum foil, and dried at 80℃ under vacuum for 12h. The mass of active material per unit area was ≈42.80mg / cm 2 Among them, Na3V 1.76 Sb 0.06 Ti 0.18 The preparation method of O(PO4)2F2 positive electrode material is as follows: vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, antimony trioxide, antimony acetate and titanium trioxide are crushed and mixed in a pulverizer in a ratio of 0.9:0.9:2:0.5:0.1:0.1 (wherein the molar ratio of antimony trioxide to antimony acetate is 1:1), and then calcined in an argon atmosphere at a sintering temperature of 600°C, a heating rate of 5°C / min, and a sintering time of 6h to obtain Na3V 1.76 Sb 0.06 Ti 0.18 O(PO4)2F2 positive electrode material was characterized by ICP, which proved that the synthesized material was Sb and Ti co-doped positive electrode material.

[0087] (2) Preparation of negative electrode sheet: Weigh 460 g of hard carbon negative electrode material (active material), 15 g of Super-P (conductive carbon), 12.5 g of sodium carboxymethyl cellulose (binder 1) and 12.5 g of styrene-butadiene rubber (binder 2). Adjust the viscosity of the slurry to 5000 mPa·s by controlling the amount of deionized water added and apply it on both sides of aluminum foil. Dry it at 80 °C under vacuum for 12 h. The mass of active material per unit area is ≈15.35 mg / cm 2 .

[0088] (3) Positive and negative electrode sheet rolling: Select a 160 μm roll gap to roll the positive electrode sheet, so that the compaction density of the positive electrode sheet is 2.2 g / cm 3 ; Select a roller gap of 130 μm to roll the hard carbon negative electrode, so that the compaction density of the negative electrode sheet is 1.05 g / cm 3 After rolling, both the positive and negative electrodes show a mirror effect.

[0089] (4) Pole sheet die-cutting: The positive electrode sheet is die-cut to a positive electrode sheet with a width of 55.2 mm, a length of 85.5 mm, a tab length of 12 mm, and a width of 12 mm; the negative electrode sheet is die-cut to a negative electrode sheet with a width of 57.2 mm, a length of 87.0 mm, and a tab length of 12 mm.

[0090] (5) Pre-sodium treatment of positive electrode: Under an inert atmosphere, 10 positive electrode sheets were immersed in a 1 mol / L biphenyl-sodium solution for 1 h, then washed three times with ethylene glycol dimethyl ether solution, and vacuum dried at 80 °C for 12 h to obtain pre-sodium positive electrode sheets.

[0091] (6) Preparation of sodium ion soft pack battery: 10 pre-sodium positive electrode sheets, celgard2500 separator, and 11 negative electrode sheets are stacked in a "Z-shaped" order, fixed with electrolyte-resistant tape, and then welded together with the aluminum tabs and the tabs using an ultrasonic spot welder. After welding the tabs, the battery cell is placed in a semi-open aluminum plastic film for top and side sealing and then transferred to an 80°C vacuum oven for drying for 6 hours; after drying, the electrolyte is injected into the battery cell, the electrolyte concentration is 1 mol / L, the solute is sodium hexafluorophosphate, the solvent is diethylene glycol dimethyl ether (G2), the additive is vinyl carbonate (VC), V(G2):V(VC)=1:0.05, and a polyanion sodium ion soft pack battery is obtained after packaging.

[0092] (7) Sodium ion soft-pack battery formation: The assembled soft-pack battery was placed in a 40°C vacuum oven for 12 h and then formed on a blue-power charge and discharge tester with a voltage range of 0.2-4.3 V. The formation conditions were: (1) 0.05C constant current charging to 3.8 V; (2) 0.1C constant current charging to 4.3 V; (3) 0.1C constant current discharging to 0.2 V.

[0093] Sodium ion soft pack battery test:

[0094] The formed sodium ion soft pack battery was vacuum vented and then pressurized for testing. The double-sealed battery was placed on a blue-electric charge and discharge tester for electrochemical performance testing. The cycle was carried out at a 0.5C rate, 1C = 129mA / g, and the voltage range was 1.5-4.2V.

[0095] Figure 6 The formation and first cycle charge and discharge curves of the sodium ion soft pack battery prepared in Example 3 of the present invention. Figure 7 The cycle performance (0.5C rate) of the sodium ion soft-pack battery prepared in Example 3 of the present invention.

[0096] The sodium ion soft-pack battery designed in Example 3 of the present invention has a capacity of 2Ah, and a capacity of 1.86Ah at the first cycle of 0.1C; the capacity retention rate after 95 cycles at a rate of 0.5C is 87.5%, and the mass energy density is 131.2Wh / kg.

[0097] Example 4

[0098] A method for preparing a polyanion sodium ion soft pack battery, the steps are as follows:

[0099] (1) Preparation of positive electrode sheet: Active material, conductive carbon, binder 1 and binder 2 were mixed in a mass ratio of 91:5:2:2. 1.88 Sb 0.03 Ti 0.09 O(PO4)2F2 positive electrode material (active material), 25g Super-P (conductive carbon), 10g sodium carboxymethyl cellulose (binder 1) and 10g styrene-butadiene rubber (binder 2) were mixed, and the viscosity of the slurry was adjusted to 6000mPa·s by controlling the amount of deionized water added and coated on both sides of aluminum foil, and dried at 80℃ under vacuum for 12h. The mass of active material per unit area was ≈42.80mg / cm 2 Among them, Na3V 1.88 Sb 0.03 Ti 0.09 The preparation method of O(PO4)2F2 positive electrode material is as follows: vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, antimony trioxide, antimony acetate and titanium trioxide are crushed and mixed in a pulverizer at a ratio of 0.95:0.95:2:0.5:0.05:0.05 (wherein the molar ratio of antimony trioxide to antimony acetate is 1:1), and then calcined in an argon atmosphere at a sintering temperature of 600°C, a heating rate of 5°C / min, and a sintering time of 6h to obtain Na3V 1.88 Sb 0.03 Ti 0.09 O(PO4)2F2 positive electrode material was characterized by ICP, which proved that the synthesized material was Sb and Ti co-doped positive electrode material.

[0100] (2) Preparation of negative electrode sheet: Weigh 460 g of hard carbon negative electrode material (active material), 15 g of Super-P (conductive carbon), 12.5 g of sodium carboxymethyl cellulose (binder 1) and 12.5 g of styrene-butadiene rubber (binder 2). Adjust the viscosity of the slurry to 5000 mPa·s by controlling the amount of deionized water added and apply it on both sides of aluminum foil. Dry it at 80 °C under vacuum for 12 h. The mass of active material per unit area is ≈15.35 mg / cm 2 .

[0101] (3) Positive and negative electrode sheet rolling: Select a 160 μm roll gap to roll the positive electrode sheet, so that the compaction density of the positive electrode sheet is 2.2 g / cm 3 ; Select a roller gap of 130 μm to roll the hard carbon negative electrode, so that the compaction density of the negative electrode sheet is 1.05 g / cm 3 After rolling, both the positive and negative electrodes show a mirror effect.

[0102] (4) Pole sheet die-cutting: The positive electrode sheet is die-cut to a positive electrode sheet with a width of 83 mm, a length of 163 mm, a tab length of 12 mm, and a width of 12 mm; the negative electrode sheet is die-cut to a negative electrode sheet with a width of 85 mm, a length of 165 mm, and a tab length of 12 mm.

[0103] (5) Pre-sodium treatment of positive electrode: Under an inert atmosphere, 18 positive electrode sheets were immersed in a 1 mol / L biphenyl-sodium solution for 1 h, then washed three times with ethylene glycol dimethyl ether solution, and vacuum dried at 80 °C for 12 h to obtain pre-sodium positive electrode sheets.

[0104] (6) Preparation of sodium ion soft pack battery: 18 pre-sodium positive electrode sheets, celgard2500 separator, and 19 negative electrode sheets are stacked in a "Z-shaped" order, fixed with electrolyte-resistant tape, and then welded together with the aluminum tabs and the tabs using an ultrasonic spot welder. After welding the tabs, the battery cell is placed in a semi-open aluminum plastic film for top and side sealing and then transferred to an 80°C vacuum oven for drying for 6 hours; after drying, the electrolyte is injected into the battery cell, the electrolyte concentration is 1 mol / L, the solute is sodium hexafluorophosphate, the solvent is diethylene glycol dimethyl ether (G2), the additive is vinyl carbonate (VC), V(G2):V(VC)=1:0.05, and a polyanion sodium ion soft pack battery is obtained after packaging.

[0105] (7) Sodium ion soft-pack battery formation: The assembled soft-pack battery was placed in a 40°C vacuum oven for 12 h and then formed on a blue-power charge and discharge tester with a voltage range of 0.2-4.3 V. The formation conditions were: (1) 0.05C constant current charging to 3.8 V; (2) 0.1C constant current charging to 4.3 V; (3) 0.1C constant current discharging to 0.2 V.

[0106] Sodium ion soft pack battery test:

[0107] The formed sodium ion soft pack battery was vacuum vented and then pressurized for testing. The double-sealed battery was placed on a blue-electric charge and discharge tester for electrochemical performance testing. The cycle was carried out at a 0.1C rate, 1C = 129mA / g, and the voltage range was 1.5-4.2V.

[0108] Figure 8 The formation and first cycle charge and discharge curves of the sodium ion soft pack battery prepared in Example 4 of the present invention. Fig. 9 The cycle performance (0.1C rate) of the sodium ion soft pack battery prepared in Example 4 of the present invention.

[0109] The sodium ion soft-pack battery designed in Example 4 of the present invention has a capacity of 10Ah, and a capacity of 8.96Ah at the first cycle of 0.1C; the capacity retention rate after 20 cycles at a rate of 0.1C is 88.5%, and the battery mass energy density is 150Wh / kg.

[0110] Fig.10 This is a physical picture of the sodium ion soft-pack battery prepared in Examples 1 to 4 of the invention.

[0111] Table 1 shows the inductively coupled plasma optical emission spectrometer (ICP-OES) characterization data of the positive electrode materials synthesized in Example 1 and Example 2. Since the volume of the Sb element is too large, the molar ratio of Sb to Ti in the positive electrode material is 1:3, and the ICP results prove that the synthesized material is a Sb and Ti co-doped positive electrode material.

[0112] Table 1

[0113]

[0114] Fig.13 , Fig.14 The scanning electron microscope (SEM) and mapping diagrams of the positive electrode materials synthesized in Example 1 and Example 2 respectively show that the positive electrode materials prepared in the present invention contain Na, O, F, P, V, Sb, and Ti elements and are evenly distributed, proving that the synthesized material is a Sb and Ti co-doped positive electrode material.

[0115] Table 2 is the EDS spectrum analysis results of the positive electrode materials synthesized in Example 1 and Example 2. It can be seen that the ratios of each element in the two positive electrode materials of Example 1 and Example 2 are basically consistent with the ICP results and the ratios in the molecular formula.

[0116] Table 2

[0117]

[0118] Comparative Example 1

[0119] The only difference from Example 1 is that the positive electrode sheet is coated by N-methylpyrrolidone slurry. That is, the steps for preparing the positive electrode sheet are as follows: the conductive carbon and the binder are mixed in a mass ratio of 91:5:4, that is, 455g Na3V 1.88 Sb 0.03 Ti 0.09 O(PO4)2F2 positive electrode material (active material), 25g Super-P (conductive carbon), 20g polyvinylidene fluoride (binder), adjust the slurry viscosity to 6000mPa·s by controlling the addition amount of N-methylpyrrolidone and coat it on both sides of aluminum foil, and the rest of the steps are the same.

[0120] As shown in Table 3, the discharge specific capacity and capacity retention rate of the aqueous slurry battery (Example 1) at a 1C rate are better than those of the N-methylpyrrolidone slurry battery (Comparative Example 1).

[0121] Table 3

[0122]

[0123] Comparative Example 2

[0124] In order to verify the effectiveness of the positive electrode sodium supplementation method, button half-cells were assembled and performance verified:

[0125] The positive electrode material, conductive carbon black (Super-P) and sodium carboxymethyl cellulose (CMC) prepared in Examples 1-4 were mixed in a mass ratio of 7:2:1 and fully dispersed with H2O as solvent. The prepared positive electrode slurry was coated on one side of aluminum foil, and after drying, the sheet was punched and weighed. Under an inert atmosphere, the obtained positive electrode sheet was soaked in a 1mol / L biphenyl-sodium solution for 10s, then washed with ethylene glycol dimethyl ether solution for 3 times, and vacuum dried at 80°C for 12h to obtain a pre-sodium positive electrode sheet; then the metal sodium sheet was used as the negative electrode, the electrolyte concentration was 1mol / L, the solute was sodium perchlorate, the solvent was ethylene carbonate (EC), propylene carbonate (PC), the additive was fluoroethylene carbonate (FEC), V(EC):V(PC):V(FEC)=1:1:0.1, and assembled into a CR2032 button battery. The positive electrode material (prepared in Example 1) without pre-sodium treatment was used as the control group, and the remaining steps were the same.

[0126] The charge and discharge test was carried out on the Blue Electric Battery Test System. The voltage range was 2.0V to 4.3V. The charge and discharge capacity and the first cycle coulomb efficiency of the obtained button battery were measured at 0.1C.

[0127] The performance comparison is shown in Table 4. Compared with the non-pre-sodium positive electrode sheets (control group), the charge specific capacity, discharge specific capacity and coulombic efficiency of all pre-sodium positive electrode sheets in Examples 1-4 changed at a rate of 0.1C, and the capacity retention rate was improved after 100 cycles at a rate of 1C.

[0128] Table 4

[0129]

[0130]

[0131] Comparative Example 3

[0132] The only difference from Example 1 is that the positive electrode material is doped with Sb element alone, that is, in the positive electrode sheet preparation step, the addition ratio of titanium oxide is 0, and the other steps are the same.

[0133] As shown in Table 5, due to the synergistic effect of Ti and Sb co-doping, the rate performance of Example 1 is significantly better than the rate performance of Comparative Example 3 using Sb element alone. Through the cycle performance test at 0.5C rate, the capacity retention rate of 0.5C cycle 100 cycles in Example 1 is 94.2%, which is much higher than the capacity retention rate of 81.6% in Comparative Example 3.

[0134] Comparative Example 4

[0135] The only difference from Example 1 is that the positive electrode material is doped with Ti element alone, that is, in the positive electrode sheet preparation step, the addition ratio of antimony trioxide and antimony acetate is 0, and the other steps are the same.

[0136] As shown in Table 5, due to the synergistic effect of co-doping with Ti and Sb, the rate performance of Example 1 is significantly better than the rate performance of Comparative Example 4 using Ti element alone. Through the cycle performance test at 0.5C rate, the capacity retention rate of 0.5C cycle 100 cycles in Example 1 is 94.2%, which is higher than the capacity retention rate of 92.3% in Comparative Example 4.

[0137] Table 5

[0138]

[0139] Water stability test

[0140] The polyanionic cathode material synthesized in Example 1 was placed in deionized water and stirred for 2 days before being assembled into a button-type half-cell. The cycle performance test was then performed at a 1C charge and discharge rate to test the cycle stability of the material.

[0141] Fig.11 This is the 1C rate charge and discharge curve of the test material. The 1C first cycle discharge capacity is 114.6mAh·g -1 The discharge capacity of the 50th cycle is 112.3 mAh g -1 , the discharge capacity of the 100th cycle is 109.7 mAh g -1 , and the material used in the present invention has a high operating voltage of ~3.8V.

[0142] Fig.12 The 1C rate cycle performance curve of the test material shows that after 100 charge and discharge cycles, there is still a capacity retention rate of 95.1%, proving that the polyanion positive electrode material of the present invention has excellent water stability.

[0143] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A sodium ion soft pack battery, characterized in that: The positive electrode uses a chemical formula of Na3V 1.88 Sb 0.03 Ti 0.09 O(PO4)2F2 or Na3V 1.76 Sb 0.06 Ti 0.18 O(PO4)2F2 polyanion positive electrode material; the positive electrode plate is pre-sodium treated; the positive electrode plate uses water-based slurry as a binder; The positive electrode sheet is prepared by mixing the polyanion positive electrode material with conductive carbon, a binder and deionized water to prepare a slurry, and coating the slurry on an aluminum foil; The chemical formula is Na3V 1.88 Sb 0.03 Ti 0.09 O(PO4)2F2 or Na3V 1.76 Sb 0.06 Ti 0.18 The preparation method of the polyanionic positive electrode material of O(PO4)2F2 comprises the following steps: Vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, an antimony source and a titanium source are mixed and calcined in a protective atmosphere to obtain the chemical formula Na3V 1.88 Sb 0.03 Ti 0.09 O(PO4)2F2 or Na3V 1.76 Sb 0.06 Ti 0.18 Polyanion positive electrode material of O(PO4)2F2; When preparing Na3V 1.88 Sb 0.03 Ti 0.09 When the O(PO4)2F2 polyanion positive electrode material is used, the molar ratio of the vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, antimony source and titanium source is 1.88:1.88:4:1:0.06:0.18; when preparing Na3V 1.76 Sb 0.06 Ti 0.18 When O(PO4)2F2 polyanion positive electrode material is used, the molar ratio of the vanadyl phosphate, vanadium phosphate, sodium fluoride, sodium carbonate, antimony source and titanium source is: 1.76:1.76:4:1:0.12:0.

36.

2. The sodium ion soft pack battery according to claim 1, characterized in that: The negative electrode plate used in the sodium ion soft pack battery contains hard carbon negative electrode material.

3. The sodium ion soft pack battery according to claim 1, characterized in that: The calcination temperature is 500-700° C., and the calcination time is 4-10 hours.

4. The sodium ion soft pack battery according to claim 1, characterized in that: The antimony source includes one or more of antimony trioxide, antimony pentoxide or antimony acetate; the titanium source includes titanium monoxide, titanium dioxide or titanium trioxide.

5. The sodium ion soft pack battery according to claim 1, characterized in that: The pre-sodium treatment comprises the step of immersing the positive electrode plate in a biphenyl-sodium solution or a naphthalene-sodium solution.

6. The method for preparing a sodium ion soft pack battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: The positive electrode sheet and the negative electrode sheet are stacked, and an electrolyte is added for packaging to obtain the sodium ion soft pack battery.

Citation Information

Patent Citations

  • Multi-electron transmission vanadium-based sodium oxyfluorophosphate battery material and preparation method thereof

    CN111446449A

  • Pre-sodium-modified sodium ion battery positive electrode, and pre-sodium-modified method and application thereof

    CN112952037A